Neutrophil Gelatinase-Associated Lipocalin Levels in Early and Late Onset Preeclampsia - Onur Guralp; Nevin Tuten; Mahmut Oncul; Serdar A Acikgoz; Hakan Ekmekci; Abdullah Tuten (Gynecology Obstetrics & Reproductive Medicine)
Objective: To evaluate the serum neutrophil gelatinase-associated lipocalin levels in pregnant women with and without preeclampsia, early-onset preeclampsia and late-onset preeclampsia, preeclampsia with and without severe features, and investigate the correlation with the neonatal outcomes.